22 year old female comes in for a normal eye exam - Tolentino, Michael J. (Digital Journal of Ophthalmology, 1997)
The patient is a 22-year-old female who comes in for a routine eye examination. Her last full ophthalmic examination, including dilation, was 2 years ago which was found to be normal.